Associations of Health and Financial Literacy with Mortality in Advanced Age - Stewart, Christopher C. (Aging Clin Exp Res, 2019)
BACKGROUND: Health and financial literacy are central to older adults’ well-being and financial standing, but the relation of literacy with mortality in advanced age remains unclear. AIMS: To determine whether lower literacy, as reflected in measures of total literacy and subscales of health and financial literacy, was associated with an increased risk of mortality. METHODS: Participants were 931 community-based older adults from the Rush Memory and Aging Project (age: mean (SD) = 80.9 (7.6), range = 58.8–100.8), an ongoing, prospective observational cohort study of aging. Participants were without dementia at the time literacy was assessed. Proportional hazards models were used to determine whether literacy measures were associated with mortality. RESULTS: During up to 8 years of follow-up, 224 (24.1% of 931) participants died. In models that adjusted for age, sex, and education, lower total, health, and financial literacy were each associated with an increased risk of mortality (total literacy: HR = 1.020, 95% CI = 1.010–1.031, p < 0.001; health literacy: HR = 1.015, 95% CI = 1.008–1.023, p < 0.001; financial literacy: HR = 1.013, 95% CI = 1.003–1.023, p = 0.014). These associations persisted after additionally adjusting for income and indices of health status; however, only the association of lower health literacy with mortality persisted after further adjusting for a robust measure of global cognition. DISCUSSION: We suspect that the current associations of lower literacy with mortality reflect the detrimental effect of early pathologic brain aging on literacy. CONCLUSIONS: Lower literacy, particularly lower health literacy, is associated with mortality in advanced age.